2023
DOI: 10.1186/s40580-023-00372-8
|View full text |Cite
|
Sign up to set email alerts
|

Recent advancements of metalenses for functional imaging

Abstract: Metasurfaces can modulate light with periodically arranged subwavelength scatterers, and they can generate arbitrary wavefronts. Therefore, they can be used to realize various optical components. In particular, metasurfaces can be used to realize lenses, so-called metalenses. In the last decade, metalenses have been actively studied and developed. In this review, we firstly introduce the fundamental principles of metalenses in terms of materials, phase modulation method, and design method. Based on these princ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(6 citation statements)
references
References 172 publications
0
6
0
Order By: Relevance
“…The NLED is also expected to find extensive applications in high‐resolution medical imaging and display [ 206,244 ] such as fluorescence microscope (Figure 23 (d)). In vivo, optical imaging with integrated high‐resolution holds great promise as a potential application for metalens.…”
Section: Prospects Of Metalens In the Future Displaymentioning
confidence: 99%
“…The NLED is also expected to find extensive applications in high‐resolution medical imaging and display [ 206,244 ] such as fluorescence microscope (Figure 23 (d)). In vivo, optical imaging with integrated high‐resolution holds great promise as a potential application for metalens.…”
Section: Prospects Of Metalens In the Future Displaymentioning
confidence: 99%
“…Complementing spatial computing, binocular metalens 3 offers a breakthrough approach to depth sensing and imaging with the advantages of being lightweight 4,5 , thin, and compact. Meta-lens create advanced optical functionalities that surpass the limitations of traditional optics 6,7 , such as wavefront shaping 8 , polarization control 9−11 , and spectral manipulation 12,13 .…”
Section: Introductionmentioning
confidence: 99%
“…3 Notably, many advancements in superlens and metalens have been achieved in recent years. 4,5 Among these technologies, superlenses, by combining micron spheres with a traditional microscope, offer a promising avenue for cost-effective super-resolution imaging by surpassing the diffraction barrier. 6−9 These microspheres can serve as microlenses to amplify the images of objects, mainly through virtual imaging.…”
mentioning
confidence: 99%
“…The pursuit of noninvasive and high-resolution dynamic imaging of biological samples is of important in life science and biomedical research, facilitating the study of dynamic cellular behaviors and observations at the subcellular level, which are often beyond the diffraction limitation of traditional optical microscopes by far-field imaging. , While electron microscopy provides high resolution, it poses challenges in terms of invasiveness and the inability to capture dynamic imaging of living cells . Notably, many advancements in superlens and metalens have been achieved in recent years. , Among these technologies, superlenses, by combining micron spheres with a traditional microscope, offer a promising avenue for cost-effective super-resolution imaging by surpassing the diffraction barrier. These microspheres can serve as microlenses to amplify the images of objects, mainly through virtual imaging. Other theories, including the Mie scattering theory, evanescent wave conversion theory, and photonic nanojet, are also proposed to explain this phenomenon. Since the micro- and nanosphere’s resolving capacity is found to be beyond the diffraction limit by Lee et al and Wang et al, , many applications are demonstrated.…”
mentioning
confidence: 99%